2009
DOI: 10.1177/1088357609344430
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Social Initiations of Preschoolers With Autism Spectrum Disorders Using Video Self-Modeling

Abstract: Video self-modeling (VSM) has accumulated a relatively impressive track record in the research literature across behaviors, ages, and types of disabilities. Using only positive imagery, VSM gives individuals the opportunity to view themselves performing a task just beyond their present functioning level via creative editing of videos using VCRs or video software. In this study, the authors used a single-subject multiple-baseline design across four preschool children on the autism spectrum to determine if self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 37 publications
2
65
0
1
Order By: Relevance
“…The number of independent mands remained high in all three sessions (M=16; range, [12][13][14][15][16][17][18][19][20][21]. He also greeted the peer at the start of each session.…”
Section: Lilymentioning
confidence: 99%
See 2 more Smart Citations
“…The number of independent mands remained high in all three sessions (M=16; range, [12][13][14][15][16][17][18][19][20][21]. He also greeted the peer at the start of each session.…”
Section: Lilymentioning
confidence: 99%
“…Video feedback consists of the participant watching non-edited videos of their own behavior and then co-reviewing it with the teacher to evaluate the behavior(s) and to discuss adjustments in future performance [11]. Video self-modeling has proven effective for spontaneous requesting of young children with autism to adults [12], vocal and physical initiations with typical peers in a playground setting [13] and social engagement [14] and social initiations with typical peers [15,16]. Evidence for video feedback has also been demonstrated to improve social initiations of children with autism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with autism who have functional speech have been found to demonstrate an understanding of wh-questions by 54 months [5]. Jones and Schwartz found that children with high functioning autism have difficulty requesting information to maintain a conversational topic.…”
Section: Introductionmentioning
confidence: 99%
“…The list of video modeling achievements is growing fast and includes, for example, teaching of functional living skills [34][35][36][37]; conversational skills [16,[38][39][40]; social language (expressive) skills [41][42][43]; academic skills [44,45]; perspective taking [46,47]; socially relevant behaviors and play skills [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]; iPod use [65]; generalized imitation skills [66]; or transitional behaviors [67].…”
Section: Introductionmentioning
confidence: 99%